Pengaruh Sikap Skeptisisme Profesional, Interpersonal Skill, dan Pengetahuan Auditor terhadap Kemampuan Pendeteksian Fraud (Studi Kasus pada Perwakilan BPKP Provinsi Sulawesi Utara) - Aruperes, Christicia Risa; Roekhudin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Corruption which is classified as a form of fraud is still a problem that is the main enemy in Indonesia. As the government's internal auditor, BPKP is responsible for carrying out fraud detection. This study aims to explain the effect of professional skepticism, interpersonal skills, and knowledge of auditors on the ability to detect fraud. This research is explanatory research. The population studied were all auditors at BPKP Representatives of North Sulawesi Province, with as many as 69 auditors. The data in this study were collected using a survey method. The data that has been collected was analyzed using multiple linear regression analysis techniques in SPSS version 21. The results showed that professional skepticism had no significant effect on the ability to detect fraud. Interpersonal skills and knowledge of auditors have a significant effect on the ability to detect fraud.